Essential concepts of cross-cultural management building on what we all share - Beer, Lawrence A. ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2012)
The purpose and/or promotional promise of almost all textbooks concerning the global environment of commerce is to help the reader understand and appreciate the economic, political, and technological context in which international business operates. This defined approach is tantamount to placing three wheels on a car and expecting it to drive smoothly. It cannot be operated without the balance that a fourth one provides, and that required wheel is culture. In the modern era of globalization, managers venturing forth to engage alien societies must be armed with cross-cultural skill sets lest they travel on feet of clay. Most academic texts and encased individual chapters targeting business students are awash with a confusing maze of intersecting theoretical-based value determinants to define and characterize cultural differences. On the other side of the culture subject are multitudes of guidebooks for executives led by the popular series Kiss, Bow or Shake Hands highlighting disparities as one does business in countless singular societies around the world. Both approaches center on memorizing collections of applied principles and/or factual orientations. A more concise, simple, and practical approach is required that cuts through the complicated cultural matrix.
Introduction -- Section 1. The basics of culture -- 1. What is culture, where does it come from? -- 2. Culture and the commercial interloper -- 3. Approaches to cross-cultural understanding -- Section 2. Analyzing cross-cultural determinants -- 4. The Janus pedagogy -- 5. Filtering the cultural determinant milieu -- Section 3. Putting it all together -- 6. Cultural navigation techniques -- 7. Final thoughts -- Notes -- Bibliography of recommended cases on cross-cultural studies -- References -- Index.
Part of: 2012 digital library.
Includes bibliographical references (p. 169-172) and index.
Also available in print.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Keywords: International business enterprises; Intercultural communication; Globalization; International business; globalization; cultural anthropology; cultural determinants; cultural dimensions; international trade; cultural diversity; cultural encounters; Electronic books